Pengaruh Mental Discounting Terhadap Keputusan Pembelian Konsumen Di Tiktokshop Dan Implikasinya Terhadap Pencatatan Pendapatan Dan Diskon Penjualan - Naura, Aisyah Rahma; Yuliati, Anik (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study aims to examine the effect of mental discounting and price on consumer purchasing decisions on the TikTok Shop platform, with sales discounts as a moderating variable and its implications for revenue recognition. A quantitative approach was employed using a survey method involving 120 student respondents with prior online shopping experience, and data were analyzed through PLS-SEM. The findings reveal that mental discounting has a positive and significant impact on purchasing decisions, price also significantly affects purchasing decisions, and sales discounts strengthen the influence of mental discounting on purchasing decisions. Furthermore, purchasing decisions significantly affect revenue recognition in accordance with applicable accounting standards. These results highlight that discount strategies in social commerce not only influence consumer behavior but also affect the transparency and reliability of financial reporting. Academically, this study contributes to interdisciplinary literature by integrating consumer behavior and accounting practices, while practically offering recommendations for e-commerce businesses to design effective promotional strategies that are aligned with accounting principles.